Energy Trading of Renewable Energy from Malaysia to Singapore - Wan Choy Chee; Wai Shin Ho; Haslenda Hashim; Lek Keng Lim (Chemical Engineering Transactions)
Sustainable energy planning and development are necessary to move towards net zero emissions. Cross-border electricity trading and green hydrogen trading are sustainable options to increase renewable energy capacity growth. Using the solar energy potential in Peninsular Malaysia, the hydropower potential in East Malaysia as an energy supply source, and the electricity demand of Singapore as the demand side, this study aimed to reveal the potential electricity and hydrogen trading activities within these two countries. A mixed integer non-linear programming mathematical model with an objective function to minimize the overall cost was developed using the General Algebraic Modeling System. The results shows that hydropower-generated electricity from East Malaysia is most cost-effective in satisfying Singapore's electricity demand, with a total cost of 1.15 × 1011 USD, resulting in an LCOE of 0.1203 USD/kWh. The deployment of a new hydropower plant capacity was found to be 6.54 GW, with annual electricity production of 36.6 TWh to satisfy the electricity demand of Singapore. This study also found that energy trading in the form of electricity transmission via submarine power cable from East Malaysia results in the lowest cost, followed by electricity transmission via power cable from Johor, and hydrogen pipeline transportation from Johor. Hydrogen shipping from East Malaysia is infeasible due to limited hydropower resource available. The model developed from this study can provide insight for policymakers, investors, and developers in the early stages of project development.